Effect of roughness on bonding performance between Portland cement concrete and magnesium phosphate cement concrete. (14th March 2022) - Zhang, Suhui; Li, Qiuyi; Yuan, Qiang; Yang, Shangfu; Dai, Xiaodi
Highlights: The effect of roughness on bonding performance between old OPC concrete and new MPC concrete was studied. Fractal dimension was used to define the roughness of the bonding surface. Roughness has significant influence on the bonding strength and microstructure of interface between new and old concretes. Abstract: This paper investigated the bonding performance between magnesium phosphate cement concrete (MPC) and ordinary portland cement concrete (OPC) with different roughness. The bonding interface was characterized using fractal dimension, backscattered electronic microscopy, and microhardness. The optimal mixture proportion of MPC is selected with the mass ratio of MgO-KH2 PO4 (M/P) by 3:1 and Na2 B4 O7 ·10H2 O-MgO (B/M) by 40%, which has the compressive strength of 52.8 MPa and the initial setting time of 24 min 20 s. It is found that the roughness indicated by fractal dimension has a positive correlation to rough depth and the bonding performance. The bonding interface can be categorized into two forms that either MPC paste bonds to OPC paste or bonds to the aggregate. Micro-analysis shows that the former has denser hydration products and lower porosity, providing better chemical bonding and the latter contributes to the mechanical interlocking which is the major form of the bonding force. MPC is a potential material for the field application of wet joints of the floating slab tracks.